Feracol paste bait for possum control a cage trial - Morgan, D.R.; Rhodes, A.T. (New Zealand Plant Protection, 2000)
Consumption and efficacy of FeraCol paste (containing 04 cholecalciferol) were assessed in a cage trial by presenting 20 captive possums with 18 g of paste a quantity predicted to be suitable for lowhazard use when presented in small paper bags attached to trees All possums ate some paste and 90 were killed The two survivors had both eaten moderate amounts of paste suggesting that it may be necessary to reassess the concentration of cholecalciferol once reliable data are gained from actual field use Consumption of FeraCol paste induced a stopfeed effect which together with its durable nature should permit use of the product in a relatively costeffective manner with low environmental risk